PHYTOCHEMICAL SCREENING AND IN VITRO ANTIMICROBIAL ACTIVITY OF AQUEOUS AND ETHANOL EXTRACTS FROM MUCUNA PRURIENS HUSKS AGAINST SOME FOODBORNE MICROORGANISMS - Omotade OGUNREMI (Stefan cel Mare University of Suceava, 2018)
Recently, plant by-products are being explored as safe and sustainable sources of bioactive compounds. This is the first study to screen phytochemicals and evaluate the antimicrobial activity of extracts from Mucuna pruriens husk for potential application as food preservative. Aqueous and ethanol extract from Mucuna pruriens seed husk were examined for presence of phytochemicals. The antimicrobial activities of the extracts against the predominant food spoilage bacterial and fungal isolates were evaluated by agar well diffusion method. Flavonoids, phenol, glycosides, steroids, saponins and anthraquinones were present in both aqueous and ethanol extracts while tannins and phlobatannins were absent. The test isolates except Candida sp. FY22 were sensitive to at least one extract. Aqueous extracts showed stronger and wider spectrum of antimicrobial activity with 100 mg/ml of the extract demonstrating highest activity index of 1.15 compared to gentamycin (10 µg) against Pseudomonas sp. BB22. This study confirms the potential of extracts from Mucuna pruriens husk as a natural source food preservative.